2018
DOI: 10.3892/or.2018.6241
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostin B42 attenuates trichostatin A-mediated resistance in pancreatic cancer cells by antagonizing IL-6/JAK2/STAT3 signaling

Abstract: Drug-resistance is the key reason for the ineffectiveness of chemotherapy in pancreatic cancer. Thus, it is very important to explore the molecular mechanisms of drug‑resistance and the methods of effective intervention. In the present study, we investigated the effect of tyrphostin B42, also called AG490, on histone deacetylase (HDAC) inhibitor trichostatin A (TSA)‑induced resistance in pancreatic cancer cells (PCCs). Evidence from phase contrast microscope revealed that TSA‑resistant cells (PANC‑1‑TSA) had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Assuming that STAT3 inactivation participates in Stattic-induced inhibition of pancreatic cancer cell metastasis, we next sought to determine whether activating STAT3 reverses the antineoplastic effects of Stattic. First, we treated cells using IL-6, a STAT3 agonist [39]. As expected, IL-6 not only induced JAK2 phosphorylation in PANC-1 and BxPc-3 cells after Stattic treatment, but also promoted STAT3 phosphorylation (Fig.…”
Section: Activating Stat3 Abolishes Stattic-mediated Inhibition Of Pcc Invasion and Migration Independent Of Tgf-β/smad Signalingsupporting
confidence: 61%
“…Assuming that STAT3 inactivation participates in Stattic-induced inhibition of pancreatic cancer cell metastasis, we next sought to determine whether activating STAT3 reverses the antineoplastic effects of Stattic. First, we treated cells using IL-6, a STAT3 agonist [39]. As expected, IL-6 not only induced JAK2 phosphorylation in PANC-1 and BxPc-3 cells after Stattic treatment, but also promoted STAT3 phosphorylation (Fig.…”
Section: Activating Stat3 Abolishes Stattic-mediated Inhibition Of Pcc Invasion and Migration Independent Of Tgf-β/smad Signalingsupporting
confidence: 61%
“…E-cadherin, N-cadherin and ZEB2 are generally regarded as the downstream molecules of the JAK2/STAT3 signaling pathway [ 29 31 ]. Several studies have shown that JAK2/STAT3 can be activated by several chemokines including CXCL3, CCL20, CXCL9, and IL-6 [ 32 35 ]. However, the interplay between CCL18 and the JAK2/STAT3 signaling pathway remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In cells, ARF6 recycles between GTP-bound (active) and GDP-bound (inactive) forms that are regulated by guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) [4]. In humans, 15 GEFs have been con rmed and sorted into 6 families (Cytohesin 1-4, EFA6A-D, BRAG1-3, BIG1/2, GBF, FBX8). All GEFs have a common Sec7 domain.…”
Section: Introductionmentioning
confidence: 99%